Optimum and stepped care standardised antihypertensive treatment with or without renal denervation for resistant hypertension (DENERHTN): a multicentre, open-label, randomised controlled trial. Issue 9981 (16th May 2015) - Azizi, Michel; Sapoval, Marc; Gosse, Philippe; Monge, Matthieu; Bobrie, Guillaume; Delsart, Pascal; Midulla, Marco; Mounier-Véhier, Claire; Courand, Pierre-Yves; Lantelme, Pierre; Denolle, Thierry; Dourmap-Collas, Caroline; et al.
Summary: Background: Conflicting blood pressure-lowering effects of catheter-based renal artery denervation have been reported in patients with resistant hypertension. We compared the ambulatory blood pressure-lowering efficacy and safety of radiofrequency-based renal denervation added to a standardised stepped-care antihypertensive treatment (SSAHT) with the same SSAHT alone in patients with resistant hypertension. Methods: The Renal Denervation for Hypertension (DENERHTN) trial was a prospective, open-label randomised controlled trial with blinded endpoint evaluation in patients with resistant hypertension, done in 15 French tertiary care centres specialised in hypertension management. Eligible patients aged 18–75 years received indapamide 1·5 mg, ramipril 10 mg (or irbesartan 300 mg), and amlodipine 10 mg daily for 4 weeks to confirm treatment resistance by ambulatory blood pressure monitoring before randomisation. Patients were then randomly assigned (1:1) to receive either renal denervation plus an SSAHT regimen (renal denervation group) or the same SSAHT alone (control group). The randomisation sequence was generated by computer, and stratified by centres. For SSAHT, after randomisation, spironolactone 25 mg per day, bisoprolol 10 mg per day, prazosin 5 mg per day, and rilmenidine 1 mg per day were sequentially added from months two to five in both groups if home blood pressure was more than or equal to 135/85 mm Hg. The primary endpoint was the mean change in daytime systolic blood pressure from baseline to 6 months as assessed by ambulatory blood pressure monitoring. The primary endpoint was analysed blindly. The safety outcomes were the incidence of acute adverse events of the renal denervation procedure and the change in estimated glomerular filtration rate from baseline to 6 months. This trial is registered withClinicalTrials.gov, numberNCT01570777 . Findings: Between May 22, 2012, and Oct 14, 2013, 1416 patients were screened for eligibility, 106 of those were randomly assigned to treatment (53 patients in each group, intention-to-treat population) and 101 analysed because of patients with missing endpoints (48 in the renal denervation group, 53 in the control group, modified intention-to-treat population). The mean change in daytime ambulatory systolic blood pressure at 6 months was −15·8 mm Hg (95% CI −19·7 to −11·9) in the renal denervation group and −9·9 mm Hg (−13·6 to −6·2) in the group receiving SSAHT alone, a baseline-adjusted difference of −5·9 mm Hg (−11·3 to −0·5; p=0·0329). The number of antihypertensive drugs and drug-adherence at 6 months were similar between the two groups. Three minor renal denervation-related adverse events were noted (lumbar pain in two patients and mild groin haematoma in one patient). A mild and similar decrease in estimated glomerular filtration rate from baseline to 6 months was observed in both groups. Interpretation: In patients with well defined resistant hypertension, renal denervation plus an SSAHT decreases ambulatory blood pressure more than the same SSAHT alone at 6 months. This additional blood pressure lowering effect may contribute to a reduction in cardiovascular morbidity if maintained in the long term after renal denervation. Funding: French Ministry of Health.